Features and Psychological Mechanisms of Professional Interaction of Participants of Criminal Process - Bulgakov, A.V.; Ekimova, V.I.; Kokurin, A.V.; Orlova, E.A.; Shashkova, I.A. (Psihologiâ i pravo, 2019)
The article presents the results of the study of psychological characteristics of professional interaction of participants in the criminal process: investigators or investigators (depending on the type of crime), forensic specialists, victims accused of various types of criminal offenses (murder, theft, hooliganism, traffic accident). The empirical base of the research was formed on the material of psychological examination of participants of 90 situations of crime scene or incident examination and further actions on disclosure of 4 types of crimes: murder, theft, hooligan actions, traffic accident. The study surveyed 315 people, including employees of the OVD - 180 people (90 persons investigators, criminologists 90 people) are the victims — 70 persons, suspects — 65 people). On the basis of the data obtained, a three-factor model of the psychological mechanisms of PV used by investigators in interaction with a group of victims, as well as a three-factor model of the psychological mechanisms of professional interaction of a group of victims in case of theft, was constructed. The conducted research allowed to reveal experimentally the structure of professional competences of investigators (investigators) and forensic specialists, as well as contradictions of the inquiry stage for each professional group in the process of professional interaction. В статье приводятся результаты исследования психологических особенностей профессионального взаимодействия участников уголовного процесса: дознавателей или следователей (в зависимости от вида преступления), специалистов-криминалистов, потерпевших, обвиняемых в различных видах уголовных преступлений (убийство, кража, хулиганство, дорожно-транспортное происшествие). Эмпирическая база исследования была сформирована на материале психологического обследования участников 90 ситуаций осмотра места преступления или происшествия и дальнейших действий по раскрытию четырех видов преступлений: убийство, воровство, хулиганские действия, дорожно-транспортное происшествие. Было обследовано 315 человек, из них сотрудники ОВД — 180 человек (дознаватели —90 человек, криминалисты — 90 человек), потерпевшие — 70 человек, подозреваемые — 65 человек). На основе полученных данных построена трехфакторная модель используемых дознавателями (следователями) психологических механизмов профессионального взаимодействия (ПВ) во взаимодействии с группой потерпевших, а также трехфакторная модель психологических механизмов профессионального взаимодействия группы потерпевших при краже. Проведенное исследование позволило экспериментальным путем выявить структуру профессиональных компетенций дознавателей (следователей) и специалистов-криминалистов, а также противоречия стадии дознания для каждой профессиональной группы в процессе профессионального взаимодействия.